Synthesis and characterization of photo-crosslinked poly(carbonate anhydrides) - B. van Bochove; J. V. Seppala (eXPRESS Polymer Letters)
Biodegradable poly(carbonate anhydrides) based on poly(trimethylene carbonate) were synthesized by ring-opening polymerization. The hydroxyl-terminated oligomers were acid-functionalized with succinic anhydride and subsequently methacrylated to obtain photo-crosslinkable three-armed macromers with anhydride bonds. The degree of acid-functionalization was over 96%, and the degree of methacrylation was over 80%. The macromers were photo-crosslinked into networks at room temperature in a nitrogen atmosphere. In vitro degradation experiments in phosphate-buffered solution (pH 7.4) at 37 °C showed that the networks degraded rapidly with complete mass loss within 72 h. For networks prepared from the higher molecular weight, the presence of an alkenyl chain in the anhydride bond resulted in lower water uptake and consequently in a decrease in the degradation rate. The degradation mechanism of these networks showed characteristics of surface erosion.